2016
DOI: 10.1186/s12903-016-0254-4
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and attitude toward using dental magnification among dental students and residents at King Abdulaziz University, Faculty of Dentistry

Abstract: BackgroundThe authors conducted a study aimed to assess the awareness and attitude among dental students and residents at King Abdulaziz University, Faculty of Dentistry (KAUFD) toward using dental magnification.MethodsAn e-questionnaire was formulated then sent to dental students and residents (n = 651). The questionnaire included questions that assessed both the awareness and attitude toward using dental magnification. Data were analyzed using IBM SPSS version 22. The chi-square test was used to establish re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 22 publications
3
29
2
Order By: Relevance
“…Even if the use of loupes was found to be increasing among qualified practitioners and dental students in the UK, the use of loupes among dental trainers and trainees remained low 24 . Alhazzazi et al found, in one dental school, a continued lack of understanding and reduced exposure to dental loupes during undergraduate education in restorative dentistry in comparison with endodontics 25 …”
Section: Discussionmentioning
confidence: 99%
“…Even if the use of loupes was found to be increasing among qualified practitioners and dental students in the UK, the use of loupes among dental trainers and trainees remained low 24 . Alhazzazi et al found, in one dental school, a continued lack of understanding and reduced exposure to dental loupes during undergraduate education in restorative dentistry in comparison with endodontics 25 …”
Section: Discussionmentioning
confidence: 99%
“…increased treatment time, steep learning curve, issues with infection control and positional difficulties especially when treating the mandibular molars. [ 9 10 12 14 17 47 48 49 50 ]…”
Section: Factors That Influence the Use Of Magnificationmentioning
confidence: 99%
“…A few of the questions were taken from previously published studies which were modified and included in our questionnaire. [ 1 2 3 ]…”
Section: Methodsmentioning
confidence: 99%